Ciała protetyczne w anglosaskich utworach fantastycznonaukowych. Ujęcie posthumanistyczne - Gajewska, Grażyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The author analyzes the images of disability in science fiction literary and film. She begins by identifying areas common to science fiction–disability studies–posthumanism. She goes on to argue that in science fiction we can find stereotypical images of people with disabilities, which are based on a culturally established dichotomy: healthy, functional (as normal) versus disabled (as abnormal), and such performances that escape this dichotomy and normalization. The author distinguishes several approaches to presenting disability in science fiction: hypervisibility combined with the unusual prosthetic abilities of the bodies, the healing of disabilities, elimination, and biodiversity. Particular attention is paid to the latter approach (biodiversity/biocooperation), exemplified by the film Avatar.